EFEKTIFITAS MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENGELOLA PARTISIPASI AKTIF SISWA KELAS VIII PADA PEMBELAJARAN IPS SMP NEGERI 43 MERANGIN TAHUN PELAJARAN 2021/2022 - Anggra Melina (Fokus | Jurnal Pendidikan STKIP YPM Bangko, 2022)
The maximum learning outcomes have not been achieved, which is an important scourge that needs to be solved. The application of the Discovery Learning type cooperative learning model is thought to be able to increase student participation in learning and learning outcomes. This type of research is a quantitative experimental method. The population in this study was class VIII students in Social Studies Learning at SMP Negeri 43 totaling 52 students. Data collection techniques using observation, documentation and questionnaires. The data validity technique uses Validity Test, Reliability Test. The data analysis technique used prerequisite test. The data are Normality Test, Homogeneity Test and t Test with SPSS 21 Program. Based on the results of the study showed that. the application of the Discovery Learning model in social studies learning can increase students' active participation in learning with a significant level of 5%, with a t-table value of 2.0074, t-count data = 3.488. Testing the hypothesis test shows that tcount > t table, then the hypothesis testing shows that rejecting H0 and accepting Ha is that there are differences in student learning outcomes between the use of the Discovery Learning type of cooperative learning model and the Conventional Learning Model (lecture). Therefore, to achieve better learning outcomes, it is necessary to use more varied teaching variations by teachers